Routledge handbook of the other backward classes in India : thought, movements and development - Somanaboina, S. Somanaboina, Simhadri. 1955-; Ramagoud, Akhileshwari; Routledge, Taylor and Francis group (London ; New York, NY : Routledge, Taylor & Francis Group, 2022)
"This handbook presents an authoritative account of the development of movements, thoughts, and policies of OBCs (Other Backward Classes) in India. Despite the adoption of egalitarian principles in the Indian Constitution, caste inequalities, discrimination, and exclusionary practices against people from backward classes and other lower castes continue to haunt them in contemporary India. A comprehensive work on the politics of identity and plurality of experiences of OBCs in India, this handbook, - Features in-depth research by eminent scholars on the OBC social and political thought, OBC movements, and OBC development and policymaking; - Discusses the life, ideologies, and pioneering contributions by Gautam Buddha, Sant Kabir, Jotirao Phule, Savitribai Phule, Shahu Maharaj, Narayana Guru, B.R. Ambedkar, Ram Manohar Lohia, and E V Ramasamy Periyar, and leading social reform movements; - Examines OBC issues with case studies from various Indian states to look at issues of pre- and post- Mandal India; backward caste movements; and, reclamation of the Bahujan legacy; - Critiques public policies and programmes for the development of OBCs in India; - Reviews the status of Muslim OBCs in India and of the invisibilised nomadic communities; - Reviews the impact of globalization on the economically backward lower castes and the impact of development initiatives for the excluded people. First of its kind, this handbook will be essential reading for scholars and researchers of exclusion and discrimination studies, diversity and inclusion studies, Global South Studies, affirmative action, sociology, Indian political history, Dalit Studies, political sociology, public policy, development studies, and political studies"--
Includes bibliographical references and index.
Keywords: Social classes -- India; Social movements -- India; Women -- India -- Social conditions; Women's rights -- India; India -- Economic policy -- 21st century; India -- Social policy -- 21st century; The Routledge Handbook other Other Backward Classes In India